KEMAMPUAN PEMECAHAN MASALAH SOSIAL SISWA KELAS XI IIS SMA MUJAHIDIN PONTIANAK - Santoso, Agung; Zakso, Amrazi; Salim, Izhar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis thesis is titled "Social Problem Solving Survey of Class XI Students of IIS SMA Pontianak Mujahidin" The common problem in this study is how the social problem solving abilities of IIS Mujahidin SMA XI grade X students with sub-problems include: 1) how is the problem solving ability of social class XI students IIS Pontianak Mujahidin High School? 2) what affects the ability to solve social problems of class XI IIS Mujahidin Pontianak ?. The research method used in this study is descriptive quantitative method and the form of research using surveys. The results of one sub-problem research are: Solving Abilities Social problems of class XI IIS SMA Mujahidin Pontianak are known as 40 of 98 students who have students' social problem solving skills namely medium category of 40.81%. So that it can be seen that almost half of the 11th grade students of IIS SMA Pontianak Mujahidin have the ability to solve social problems in the medium category. the results of the two sub-problem research are: It can be seen from the indicators that affect almost 50% of the 11th grade students of IIS SMA Mujahidin Pontianak have the ability to solve social problems in the medium category. Conclusions from the results of the study: Based on the analysis of the data obtained, the researcher can answer according to the formulation of the problem by concluding the results of the study. In accordance with the results of the research data analysis, that the ability to solve social problems of class XI IIS of the Mujahidin High School in Pontianak is included in the medium category.Â Keyword : Solving Social Problems, Students.